PERLINDUNGAN HUKUM TERHADAP DOKTER DAN PASIEN DALAM PELAYANAN KESEHATAN DI INDONESIA - Prayuti, Yuyut; Lany, Arman; Waworuntu, Aprisia N.; Manueke, Sherwin F.; Dwitamma, M. Adib (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
The relationship between doctor and patient is a relationship based on the law. Practically, both doctor and patient have the same potential to experience loss or disadvantages due to one of the parties violate the obligations and rights. Treatment of disease that involves two parties – the health service provider and the patient – should be protected by law. It is to embody the highest degree of health for the community in order to achieve a strong, healthy, and productive nation. The aim of this writing is to know all matters concerning the state regulation of relationship between doctor and patient, including each party’s obligations and rights as well as legal protection for both doctor and patient. Method of this writing is qualitative descriptive by collecting data and information based on health laws in Indonesia, as well as literature research. Other source of data and information are from relevant writing such as scientific journal, thesis, books and other electronic media.